Brevican: A key proteoglycan in the perisynaptic extracellular matrix of the brain - Frischknecht, Renato; Seidenbecher, Constanze I. (International Journal of Biochemistry and Cell Biology, 2012)
Brevican is a neural proteoglycan implicated in a multitude of physiological and pathophysiological plasticity processes in the brain. It localizes to neuronal surfaces and contributes to the formation of specific types of extracellular matrix like the perineuronal nets or the perisynaptic or axon initial segment-based matrix in mature neuronal tissue. Via a variable degree of chondroitin sulfate attachment, limited proteolytic cleavage by matrix metalloproteinases, differential splicing and Ca2+-dependent binding to interaction partners it acts as a regulator in synaptic plasticity, glioma invasion, post-lesion plasticity or Alzheimer's disease. This review briefly summarizes its gene and protein structure, biochemical interactions and neurobiological functions. © 2012 Elsevier Ltd.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Extracellular matrix; Lecticans; Metalloproteinases; Neuronal plasticity; Perisynaptic matrix